2020
DOI: 10.1177/0954406220969731
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of heat-treated nano-clay-composite for improving high-cycle fatigue properties of AlSiCu aluminum alloy under stress-controlled fully-reversed bending loads

Abstract: In the present article, a heat-treated nano-clay-composite was fabricated by stir-casting to improve high-cycle bending fatigue properties of AlSiCu aluminum alloys, which have been widely used in engine cylinder-heads. For such an objective, after ball milling of nano-clay-particles with micro-copper-particles, these coated particles were added to the aluminum melt and cylindrical specimens were stir-casted. Then, fully-reversed stress-controlled fatigue testing was performed on standard samples. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 72 publications
(123 reference statements)
1
3
0
Order By: Relevance
“…Increasing the fatigue lifetime of aluminum alloys by the reinforcement was also reported by Rezanezhad et al [10], Sharifi et al [13], and Khisheh et al [14], which could be claimed as an agreement with obtained results in this research. The reason for such an improvement was due to the microstructural changes in the microstructure of the aluminum alloy.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Increasing the fatigue lifetime of aluminum alloys by the reinforcement was also reported by Rezanezhad et al [10], Sharifi et al [13], and Khisheh et al [14], which could be claimed as an agreement with obtained results in this research. The reason for such an improvement was due to the microstructural changes in the microstructure of the aluminum alloy.…”
Section: Resultssupporting
confidence: 93%
“…More details for the fabrication of the studied materials could be found in the literature by Aroo et al [1], Azadi et al [3], Rezanezhad et al [10], and Zolfaghari et al [11]. In addition, more details of fatigue testing and the geometry of standard cylindrical samples could be followed in the literature by Parast et al [12], Sharifi et al [13], and Khisheh et al [14]. After testing, a regression curve-fitting process was done for the sensitivity analysis on experimental data.…”
Section: Materials and Experimentsmentioning
confidence: 99%
“…More details of these microstructures including FE-SEM images were found in previous studies [1,3]. Azadi et al [17,38] and Shari et al [53] showed that by the presence of the reinforcement (nano-particles plus the heat treatment), the change in the Si morphology was signi cant and seemed to be the needle-shape and also the block shape. Due to the reinforcement, the Si phase percentage enhanced as 8%.…”
Section: Resultsmentioning
confidence: 64%
“…As a rst statement, the brittle fracture was seen according to the presence of cleavage and quasi-cleavage marks in all specimens under fatigue and corrosion-fatigue tests. Moreover, tear ridges, micro-cracks, and also broken intermetallics phases were also observed on the fracture surface of specimens, as also represented in the literature [13,[53][54]. As Zhang et al [55] reported, when there was a brittle facture behavior in the material, the fatigue fracture of the piston aluminum alloy happened in a perpendicular direction to the force axis.…”
Section: Resultsmentioning
confidence: 65%